Perubahan Stok Karbon dan Nilai Ekonominya pada Konversi Hutan Rawa Gambut Menjadi Hutan Tanaman Industri Pulp - Yanto Rochmayanto; Dudung Darusman; Teddy Rusolono; E Elias (Institut Pertanian Bogor (IPB University), 2010)
Peat swamp forest is an important pool of terrestrial carbon stock (C-stock). Therefore, research on change of C-stock and its economic value of peat swamp forest conversion to pulpwood industrial plantation forest is important. The objectives of this research are to know the change of C-stock on peat swamp forest conversion to pulpwood industrial plantation forest, and to get the carbon economic value of peat swamp forest and pulpwood industrial plantation forest. The result showed that conversion from logged over and secondary forest causing the decrease of C-stocks of 103.53 and 61.02 t ha-1 year-1, while conversion from degraded forest causing the increase of C-stocks of 22.47 t ha-1 year-1. REDD project on pulpwood industrial plantation forest from degraded land causing the increase of NPV of 20.21% and 51.13% for compensation prices US 9 and 12 tCO2-e-1. REDD project with conservation on secondary forest gave lower economic value than pulpwood industrial plantation forest at all compensation prices simulation, and REDD project with preservation logging gave higher economic value than pulpwood industrial plantation forest at compensation price US 12 tCO2-e-1. REDD project on logged over forest gave higher economic value than pulpwood plantation at compensation prices US 9 and 12 tCO2-e-1 (both on conservation and preservation logging scenarios).